Evidence of the simultaneous replications of active viruses in specimens positive for multiple respiratory viruses - Kawase, Miyuki; Suwa, Reiko; Sugimoto, Satoko; Kakizaki, Masatoshi; Kume, Yohei; Chishiki, Mina; Ono, Takashi; Okabe, Hisao; Norito, Sakurako; Ujike, Makoto; Hosoya, Mitsuaki; Hashimoto, Koichi; et al. (Microbiology spectrum, 2024)
Genetic diagnostic assays for the detection of respiratory viruses sometimes show simultaneous multiple infections with low copy numbers. In such cases, the disease is considered caused by a single etiologic agent and others are nonspecific reactions and/or contaminations. Interferon-dependent interference is seen in dual infections of influenza and respiratory syncytial virus, which are the main causes of respiratory infections. Virus isolation is one of the answers in detecting other active viruses present in specimens, and the air–liquid interface culture of human bronchial/tracheal epithelial cells (HBTEC-ALI) is optimal for the isolation of respiratory viruses owing to its wide range of susceptibility. In this study, we successfully confirmed the replications of various viruses from specimens with low copy numbers and simultaneous passage of two to three viruses using HBTEC-ALI cultures, mainly including human bocavirus 1 and/or human rhinovirus. Since the pandemic of coronavirus diseases 2019, the use of real-time PCR assay has become widespread among people who were not familiar with it in virus detection. As a result, whether a high real-time PCR value in one time test indicates virus transmissibly became a complicated social problem, regardless of the difference in assays and/or amplification conditions, the time and number of diagnostic test during the time course of infection. In addition, the multiple positives in the test of respiratory viruses further add to the confusion in the interpretation of the infection. To address this issue, we performed virus isolation using pediatric SARI (severe acute respiratory infections) specimens on air–liquid interface culture of human bronchial/tracheal epithelial cell culture. The result of this study can be a strong evidence that the specimens showing positivity for multiple agents in real-time PCR tests possibly contain infectious viruses.